Motivasi Sebagai Jembatan Gap Pengalaman Fresh graduate - Siswanto Siswanto; Ray Octafian (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
The main issue addressed is the significant gap between the work experience of new graduates and industry demands, where Fresh graduates often encounter obstacles in securing their first job due to the lack of practical field experience. This phenomenon creates a paradox in which companies require experienced workers, while new graduates need opportunities to gain such experience. The study employs a qualitative approach with a case study method conducted at Netjes College to gain an in-depth understanding of how motivation can serve as a compensatory factor for limited experience. The findings reveal that high intrinsic and extrinsic motivation can effectively bridge the experience gap through several mechanisms: increased willingness for independent learning, greater adaptability to new work environments, initiative in taking on additional responsibilities, and persistence in facing early career challenges. These results indicate that Fresh graduates with high motivation tend to be more proactive in seeking self-development opportunities and demonstrate competitive performance compared to candidates who possess experience but low motivation. The practical implication of this study is the importance for educational institutions to not only focus on transferring technical knowledge but also to develop students’ motivational aspects as essential preparation for transitioning from the academic world to the professional realm.